Effect of Fibrous Septa in Radiofrequency Heating of Cutaneous and Subcutaneous Tissues: Computational Study. Issue 5 (3rd June 2013) - Jimenez Lozano, Joel N.; Vacas‐Jacques, Paulino; Anderson, R. Rox; Franco, Walfre
Abstract Background and Objectives Radiofrequency (RF) energy exposure is a popular non‐invasive method for generating heat within cutaneous and subcutaneous tissues. Subcutaneous fat consists of fine collagen fibrous septa meshed with clusters of adipocytes having distinct structural, electrical and thermal properties that affect the distribution and deposition of RF energy. The objectives of this work are to (i) determine the electric and thermal effects of the fibrous septa in the RF heating; (ii) investigate the RF heating of individual fat lobules enclosed by fibrous septa; and, (iii) discuss the clinical implications. Methods and Results We used the finite element method to model the two‐dimensional, time‐dependent, electro‐thermal response of a three‐layer tissue (skin, subcutaneous fat, and muscle). We considered two different configurations of subcutaneous fat tissue: a homogenous layer of fat only and a honeycomb‐like layer of fat with septa. Architecture of the fibrous septa was anatomically accurate, constructed from sagittal images from human micro‐MRI. For a large electrode applied to the skin surface, results show that the absorbed electric power density is greater in some septa than in the surrounding fat lobules, favoring the flux of electric current density. Fibers aligned parallel to the electric field have higher electric flux and, consequently, absorb more power. Heat transfer from the septa occurs over time during and after RF energy delivery. There is a greater temperature rise in fat with fibrous septa. Conclusions The presence of septa affects the local distribution of the static electric field, facilitates the flux of electric current and enhances the bulk electric power absorption of the subcutaneous fat layer. Fibrous septa aligned with the local electric field have higher absorbed power density than septa oriented perpendicular to the electric field. Individual fat lobules gain heat instantly by local power absorption and, eventually, by diffusion from the surrounding septa. Lasers Surg. Med. 45:326–338, 2013. © 2013 Wiley Periodicals, Inc.